Predictors of underage pregnancy among women aged 15–19 in highly prevalent regions of Ethiopia: a multilevel analysis based on EDHS, 2016 - Desalegn Anmut Bitew; Yonas Akalu; Yitayeh Belsti; Mengistie Diress; Yibeltal Yismaw Gela; Daniel Gashaneh Belay; Amare Belete Getahun; Bewuketu Terefe; Mihret Getnet (Scientific Reports, 2023)
Abstract Under age (teenage) pregnancy is a pregnancy that occurs under the age of 20 years old. Its magnitude is increasing globally. It is much higher in low-income countries compared to high-income countries. Teenage pregnancy exposed teenagers to various obstetric and perinatal complications. However, its predictors are not well investigated in highly prevalent regions of Ethiopia. Therefore, this study assessed individual and community-level predictors of teenage pregnancy using a multi-level logistic regression model. An in-depth secondary data analysis was performed using the fourth Ethiopian Demographic and Health Survey (EDHS) 2016 data set. A weighted sample of 2397 teenagers was included in the final analysis. Multi co linearity and chi-square tests were checked and variables which did not fulfill the assumptions were excluded from the analysis. Four models were fitted. Variables with p value ≤ 0.2 in the bi-variable multilevel logistic regression were included in the multivariable multilevel logistic regression. The adjusted odds ratio (AOR) with a 95% confidence interval (95% CI) was computed. Variables with a p value of less than 0.05 in the multi-variable multilevel logistic regression were declared as statistically significant predictors. A total of 2397 weighted participants aged from 15 to 19 were involved. About 15% of teenagers were pregnant. Age [17 (AOR = 9.41: 95% CI 4.62, 19.13), 18 (AOR = 11.7: 95% CI 5.96, 23.16), 19 (AOR = 24.75: 95% CI 11.82, 51.82)], primary education (AOR = 2.09: 95% CI 1.16, 3.76), being illiterate (AOR = 1.80: 95% CI 1.19, 2.73), religion [being Muslims (AOR: 2.98:95% CI 1.80, 4.94), being Protestants (AOR = 2.02: 95% CI 1.20, 3.41)], contraceptive non use (AOR = 0.18: 95% CI 0.11, 0.31), a high proportion of family planning demand (AOR = 3.52: 95% CI 1.91, 6.49), and a high proportion of marriage (AOR = 4.30: 95% CI 2.25, 8.21) were predictors of teenage pregnancy. Age, educational status, religion, contraceptive non-use, literacy proportion of marriage and proportion of demand for family planning were the most significant predictors of teenage pregnancy. The ministry of education shall focus on universal access to education to improve female education. The government should work in collaboration with religious fathers to address reproductive and sexual issues to decrease early marriage and sexual initiation. Especial attention should be given to teenagers living in a community with a high proportion of marriage.